Nutritional Status of Adolescent Girls in Rural Area of Kolar District -A Cross-Sectional Study - M. Sarithareddy; A.V. Deepa; H.R. Shivaramakrishna (Al Ameen Medical College, 2011)
Objective: To assess the nutritional status of adolescent girls in selected villages of the Kolar district. Methods: A community-based cross-sectional study was carried out over a period of two months. 230 adolescent girls of age 10-19 years were selected randomly. Data was collected by interviewing the adolescent girls using predesigned and pre tested Proforma. Various statistical applications like percentiles, mean, standard deviation and proportions were used for analysis of the data. Results: The prevalence of wasting and stunting was 54.79% and 32.17% respectively as per water lows classification and the trend of wasting and stunting declines with the age. The prevalence of thinness was found to be 73.5% as per Indian standards. Prevalence of Anemia was 34.8% percent and it was more among menstruating girls than compared to non-menstruating girls. Anemia prevalence was less among adolescent girls using footwear during defecation than girls not using foot wear. Conclusion: It is concluded that there is a high prevalence of under nutrition among adolescent girls in the rural area of the selected villages. Health education and nutrition interventions are needed on priority basis.